Formation of Student Character in Islamic Religious Education Learning in High Schools During the Corona Virus Pandemic - Nursikin, Mukh; Sutrisna, Sutrisna; Nazmi, Ranti; Elliot, McCarty; Kathryn, Morse (Al-Hijr: Journal of Adulearn World, 2024)
Character is an important aspect that needs to be instilled in students in forming morals. Especially for students who have entered the upper secondary level of education. However, the corona virus pandemic makes it difficult for educators to apply distance learning, especially in cultivating student character according to Islamic religious education learning. This is because the previously face-to-face learning system has changed to online. This is what causes educators to make more efforts to instill good character in students. Therefore, the research is aimed at finding out in order to analyze what educators need to do in realizing the formation of student character during the corona virus pandemic using an online learning system. The research method uses quantitative methods (observation, interviews, distribution of questionnaires) to make it easier to collect the intended respondents. The results of this research were analyzed according to the objects obtained from the educator respondents to cultivate student character using an online system. The studies that are formed in cultivating character are cleanliness, discipline, responsibility according to the learning values of Islamic religious education. In this research, there are a few limitations felt by educators, namely regarding the lack of media and supporting applications to fulfill the cultivation of students' character by learning Islamic religious education. So it is hoped that future researchers will be able to provide media development as a means of supporting learning and making it easier for educators to shape students' character through Islamic religious education.